Overview of gender and social inclusion activities in AICCRA - Huyer, Sophia; Ouédraogo, Mathieu; Chanana, Nitya (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
AICCRA is required to integrate, monitor, and report on gender and social inclusion according to the World Bank Gender Tag System